Pengaruh Sistem Blok Perkuliahan terhadap Tingkat Motivasi Belajar Mahasiswa Fakultas Ilmu Pendidikan - Juli Hidayanti; Keisha Liviana Marta; Nazwa Angelyra; Putri Cantika Siregar; Rinby Dwi Andini; Tengku Nuraini Sukma Putri (Jurnal Pena Pendidikan Dasar, 2026)
Learning motivation is a crucial factor influencing the effectiveness of the learning process in higher education. One instructional innovation implemented in universities is the block system of lectures, in which learning activities are organized intensively for one course within a specific period before moving to another course. This study aims to examine the effect of the block lecture system on students’ learning motivation at the Faculty of Education, Universitas Negeri Medan. This research employed a quantitative approach using a field survey method. The participants consisted of 29 students, all of whom were selected as the research sample using a saturated sampling technique. Data were collected through a Likert-scale questionnaire that had been tested for validity and reliability. The data were analyzed using normality tests, correlation analysis, and simple linear regression. The results showed that the data were normally distributed and that there was a positive and significant relationship between the block lecture system and students’ learning motivation. Furthermore, the regression analysis indicated that the block lecture system had a significant effect on learning motivation, as evidenced by a significance value below 0.05. These findings suggest that the block lecture system can enhance students’ focus, independence, and engagement in learning when implemented in a well-planned and balanced manner. This study is expected to provide practical implications for higher education institutions in evaluating and developing effective learning systems that support the improvement of students’ learning motivation.